2011
DOI: 10.1093/eurheartj/ehq494
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacodynamic comparison of prasugrel vs. high-dose clopidogrel in patients with type 2 diabetes mellitus and coronary artery disease: results of the Optimizing anti-Platelet Therapy In diabetes MellitUS (OPTIMUS)-3 Trial

Abstract: AimsPatients with diabetes mellitus (DM) have increased platelet reactivity and reduced platelet response to clopidogrel compared with patients without DM. Prasugrel, a more potent antiplatelet agent, is associated with greater reductions in ischaemic events compared with clopidogrel, particularly in patients with DM. The aim of this study was to perform serial pharmacodynamic assessments of prasugrel with high-dose clopidogrel in patients with DM.Methods and resultsOptimizing anti-Platelet Therapy In diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 22 publications
7
136
2
6
Order By: Relevance
“…Numerous pharmacodynamic studies including unselected patients in terms of their baseline platelet reactivity demonstrated that prasugrel much stronger than clopidogrel, even with high doses of the latter (i.e. a loading dose of 600 mg and a maintenance dose of 150 mg), inhibits ADP-induced platelet aggregation [20,[26][27][28]. This intensified platelet inhibition by prasugrel is believed to account for the reduction of ischemic events when compared with clopidogrel therapy in ACS patients undergoing PCI which was shown in the TRITON-TIMI 38 trial [4].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacodynamic studies including unselected patients in terms of their baseline platelet reactivity demonstrated that prasugrel much stronger than clopidogrel, even with high doses of the latter (i.e. a loading dose of 600 mg and a maintenance dose of 150 mg), inhibits ADP-induced platelet aggregation [20,[26][27][28]. This intensified platelet inhibition by prasugrel is believed to account for the reduction of ischemic events when compared with clopidogrel therapy in ACS patients undergoing PCI which was shown in the TRITON-TIMI 38 trial [4].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our findings, in a recently published study by Ford et al [1], where pre-and post-treatment platelet aggregation was assessed, no evidence for rebound of platelet reactivity to above baseline level was found in 171 patients. In other crossover studies of P2Y12 inhibitors for stable CAD patients [1,16] or stable CAD with diabetes [1,17], where also preand post-treatment platelet aggregation were assessed, there were no significant differences compared to baseline seven to ten days after withdrawal. Available clinical studies provided conflicting results when we consider the occurrence of clinical thrombotic events after stopping clopidogrel.…”
Section: Primary Endpointmentioning
confidence: 91%
“…LTA was performed as previously reported 9. Briefly, blood samples were collected in 3.8% sodium citrate tubes.…”
Section: Methodsmentioning
confidence: 99%